Greenland blocking index daily series 1851–2015: Analysis of changes in extremes and links with North Atlantic and UK climate variability and change. (6th April 2018) - Hanna, Edward; Hall, Richard J.; Cropper, Thomas E.; Ballinger, Thomas J.; Wake, Leanne; Mote, Thomas; Cappelen, John
Abstract : We present a homogenized Greenland blocking index (GBI) daily record from 1851 to 2015, therefore significantly extending our previously published monthly/seasonal GBI analysis. This new time series is analysed for evidence of changes in extreme events, and we investigate the underlying thermodynamic and dynamic precursors. We compare occurrences and changes in extreme events between our GBI record and a recently published, temporally similar daily North Atlantic Oscillation (NAO) series, and use this comparison to test dynamic meteorology hypotheses relating negative NAO to Greenland blocking. We also compare daily GBI changes and extreme events with long‐running indices of England and Wales temperature and precipitation, to assess potential downstream effects of Greenland blocking on UK extreme weather events and climate change. In this extended analysis we show that there have been sustained periods of positive GBI during 1870–1900 and from the late 1990s to present. A clustering of extreme high GBI events since 2000 is not consistently reflected by a similar grouping of extreme low NAO events. Case studies of North Atlantic atmospheric circulation changes linked with extreme high and low daily GBI episodes are used to shed light on potential linkages between Greenland blocking and jet‐stream changes. Particularly noteworthy is a clustering of extreme high GBI events during mid‐October in 4 out of 5 years during 2002–2006, which we investigate from both cryospheric and dynamic meteorology perspectives. Supporting evidence suggests that these autumn extreme GBI episodes may have been influenced by regional sea‐ice anomalies off west Greenland but were probably largely forced by increases in Rossby‐wave train activity originating from the tropical Pacific. However, more generally our results indicate that high GBI winter anomalies are co‐located with sea‐ice anomalies, while there seems to be minimal influence of sea‐ice anomalies on the recent significant increase in summer GBI. Abstract : Since 2000 there has been a sustained period of high Greenland blocking, especially in summer. Case studies of atmospheric circulation changes linked with extreme daily Greenland blocking episodes are used to shed light on linkages with North Atlantic jet‐stream changes and possible connections with extreme weather events over the UK. Particularly noteworthy is a clustering of extreme high blocking events during mid‐October in 4 out of 5 years during 2002–2006, which we investigate from both cryospheric and dynamic meteorology perspectives.